OBSERVATIONS CONCERNING THE HARMFUL ENTOMOFAUNA FROM WINTER RAPESEED CROPS IN THE CONDITIONS OF CENTRAL OF MOLDAVA, BETWEEN YEARS 2014-2017 - PAULA -LUCELIA URSACHE; ELENA TROTUS; ALEXANDRA -ANDREEA BUBURUZ (Journal of Engineering Studies and Research)
During 2014-2017, 22 species were identified in the yellow bowl trap type installed in winter rapeseed crops established at A.R.S.D. Secuieni. Of these, 11 species are specific to winter rapeseed crops and 11 species were accidental identified because of the proximity with different agricultural crops (maize. sunflower. grain cereals). The highest abundance was registered by Epicometis hirta Poda species which accounted 914 specimens collected during the analyzed period. The species were integrated into classes of dominance ((D1 - subrecedent species. D2 - recedent species. D3 - subdominant species. D4 - dominant species and D5 - eudominant species). Meligethes aeneus F., Ceuthorrhyncus napi Gyll. and Epicometis hirta Poda. being considered eudominant species belonging to the D5 class. The Ceuthorrhynchus napi Gyll., Meligethes aeneus F., Epicomites hirta Poda., Psylliodes chrysocephala L., Subcoccinella 24 punctata L., Oulema melanopa L. species were classified in the constancy class - C4 - euconstant species. Meligethes aeneus F., Epicometis hirta Poda and Ceuthorrhynchus napi Gyll. species recorded the highest values for the index of ecological significance (W %) and were classified in the W5 class - characteristic species. The collected entomofauna belongs to five orders: Coleoptera, Heteroptera, Lepidoptera,. Diptera and Hymenoptera. The highest number of species (17 species) and the highest number of collected speciemens (3246 specimens) belonged to the Coleoptera order.